A multi-variable building energy optimization: assessing the role of energy efficient lighting technology in changing the optimal window-to-wall ratio in an office building. Issue 11 (1st December 2022) - Zolfaghari, Zahra; Jones, James
ABSTRACT: Daylight harvesting is a passive strategy that helps to increase occupants' productivity, mental and physical health as well as spatial quality and energy performance. Therefore, decisions regarding windows' size and placement are extremely important in the design process. Although beneficial in many ways, large windows are not an energy-efficient design decision in many climates. While daylight admitted through windows reduces the lighting load, it can cause excessive heat flow and increased cooling load. Energy standards limit the window-to-wall ratio (WWR) to 40% to balance the heat exchange and light gain. However, this general requirement does not account for climate, building type, lighting fixtures, etc. Advancements in the lighting industry have introduced efficient lighting fixtures that can change the WWR and lighting power density (LPD) code requirements for some climates. This study used a simulation method to investigate the impact of new lighting systems on facade design, WWR, energy performance, proposed changes to the code requirements, and daylight harvesting effectiveness in presence of efficient lighting fixtures. The results suggested a lower reliance on daylight and large windows with the use of efficient lighting fixtures and proposed a revision of the 40% prescriptive requirement due to the recent upgrades in lighting systems.